การใช้เกมเพื่อพัฒนาทักษะการอ่านออกเสียงคำศัพท์ภาษาอังกฤษ ของนักเรียนชั้นประถมศึกษาปีที่ 5 โรงเรียนบ้านนาโคก จังหวัดเลย - กองศูนย์, วีรยุทธ (วารสารศรีล้านช้างปริทรรศน์; Vol 5 No 1 (2019): วารสารศรีล้านช้างปริทรรศน์ ปีที่ 5 ฉบับที่ 1 (มกราคม - มิถุนายน 2562), 2019)
การวิจัยครั้งนี้มีจุดมุ่งหมายเพื่อพัฒนาทักษะการอ่านออกเสียงคำศัพท์ภาษาอังกฤษ ประถมศึกษาปีที่ 5 ให้มีประสิทธิภาพตามเกณฑ์ 80/80 โดยหาค่าดัชนีประสิทธิภาพของการจัดกิจกรรมการเรียนรู้คำศัพท์ภาษาอังกฤษโดยใช้เกมที่มีต่อการจัดกิจกรรมการเรียนรู้คำศัพท์ภาษาอังกฤษโดยใช้เกม กลุ่มตัวอย่างคือนักเรียนชั้นประถมศึกษาปีที่ 5 โรงเรียนบ้านนาโคก อำเภอเมือง จังหวัดเลยภาคเรียนที่ 2 ปีการศึกษา 2559 จำนวน 1 ห้องเรียน จำนวน 30 คนได้มาโดยวิธีการเลือกแบบเจาะจง (Simple Random Sampling) ดำเนินการทดลอง 6 สัปดาห์ สัปดาห์ละ 4 คาบ ๆ ละ 50 นาทีรวม 24 คาบ และมีการทดสอบวัดผลการเรียนรู้โดยวิธีสลับตัวเลือกในการวัดผลการเรียนรู้แต่ละครั้ง เครื่องมือที่ใช้ ในการศึกษา แผนการสอนการใช้เกมคำศัพท์ ประกอบการสอน แบบทดสอบวัดผลการ เรียนรู้ และวัดความคงทนในการเรียนรู้คำศัพท์และแบบสอบถามความคิดเห็นเกี่ยวกับเกมคำศัพท์ 12 แผนการ สอนของนักเรียน สถิติที่ใช้ ในการวิ เคราะห์ข้อมูล คือ ร้อยละ ค่าเฉลี่ย (Mean) ค่าความเบี่ยงเบนมาตรฐาน (Standard Deviation) และ t-test           ผลการวิจัยพบว่า (1) การพัฒนาทักษะการอ่านภาษาอังกฤษ โดยการใช้เกมคำศัพท์ภาษาอังกฤษฝึกทักษะสาระการเรียนรู้ภาษาอังกฤษของนักเรียนชั้นประถมศึกษาปีที่ 5/1 มีประสิทธิภาพเท่ากับ 85.43/86.47 ซึ่งสูงกว่าเกณฑ์มาตรฐานที่ตั้งไว้ คือ 80/80 (2) ผลที่เกิดกับนักเรียนหลังการพัฒนาทักษะการอ่านภาษาอังกฤษ โดยใช้เกมคำศัพท์ภาษาอังกฤษฝึกทักษะสาระการเรียนรู้ภาษาอังกฤษ ของนักเรียนชั้นประถมศึกษาปีที่ 5 พบว่านักเรียนมีทักษะการอ่านและเขียนดีขึ้น ซึ่งส่งผลให้นักเรียนมีผลสัมฤทธิ์ทางการเรียนด้านทักษะการอ่านสูงขึ้น มีค่าเฉลี่ยร้อยละ 86.47   The purpose of English reading teaching through vocabulary games was to develop students to remember English vocabularies, to improve their reading aloud skill, and have good attitude towards English learning. The objectives of the research were to develop the reading aloud skill of English vocabularies for Prathomsuksa 5 students to the efficiency criteria of 80 / 80 and to find the efficiency indicator of English vocabulary games for Prathomsuksa 5 students towards English vocabulary games. The research samples were thirty Prathomsuksa 5 students in the academic year 2559, Ban Na Khok School, Si Song Rak Sub-district, Mueang Loei District, Loei Province, selected by the sample random sampling. The operation of the research was conducted in six weeks: four 50-minute periods per week, and there was a shuffle of multiple choices in each test. The research instruments were the lesson plan on English vocabulary games, Achievement Test, Retention Test for English Vocabulary Learning, and the questionnaire on 12 lesson plans of vocabulary games. The data were analyzed by the statistics of percentage, mean, standard deviation and T-test.             The research findings were as follows: 1. The development of English reading-aloud skill through vocabulary games for Prathomsuksa 5 students, was found to be 86.47/85.43, which was higher than the specific standard criteria of 80/80. 2. After the development of English reading aloud skill through vocabulary games, it was found that English reading and writing skills of those students were better. As a result, their achievement of reading skill was found to be at a higher level with 86.47% of mean.